CSR as a Moderator of Firm Value: Impact of GCG, Financial Performance, and Green Accounting - Mega Anggun Sari; Tantina Haryati (International Journal Of Economics Social And Technology, 2026)
The energy sector plays a strategic role in Indonesia’s economy; however, firm value in this sector is highly vulnerable to global dynamics and increasing sustainability pressures. Prior studies report inconsistent findings regarding the effects of Good Corporate Governance (GCG), financial performance, and green accounting on firm value, while research incorporating Corporate Social Responsibility (CSR) as a moderating variable remains limited. Therefore, this study aims to examine the effects of GCG, financial performance, and green accounting on firm value, with CSR as a moderating variable. This study employs a quantitative explanatory approach using secondary data derived from annual and sustainability reports of energy sector companies listed on the Indonesia Stock Exchange during the 2022–2024 period. The sample consists of 40 companies with 120 observations, selected through purposive sampling. Data were analyzed using panel data regression with model selection based on the Chow, Hausman, and Lagrange Multiplier tests, and Moderated Regression Analysis (MRA) was applied to test moderating effects. The results indicate that GCG has a positive and significant effect on firm value, financial performance is not significant, and green accounting has a negative effect. CSR does not moderate these relationships, although all variables jointly have a significant effect on firm value.